Healing spaces: a retrospective cohort study on the effect of outdoor spaces in psychiatric inpatient units on PRN medication use, seclusion/restraints, and constant observation - Liu, Kevin; Saito, Ema; Linder, Howard (Frontiers in Psychiatry, 2026)
BackgroundThis retrospective chart review investigated the differential correlation of outdoor space accessibility with as-needed(PRN) medication use, constant observation(CO), and seclusion/restraint across a geriatric psychiatry unit (Unit A) and a general psychiatry unit (Unit B). While the influence of psychiatric facility design on patient aggression has been explored, empirical investigation specifically into the correlation of outdoor space accessibility with aggression in psychiatric inpatients, remains limited.MethodsWe compared the use of oral and intramuscular PRN medications, seclusion/restraint, and CO during periods of outdoor space accessibility (2022-2023) versus inaccessibility (2024). Outdoor space was inaccessible for Unit A from January 31 to April 18, 2024, and for Unit B from February 12 to May 6, 2024. The analysis was conducted assuming no other significant confounding changes in unit operations or patient populations during the study period. A single factor ANOVA analysis was chosen, but to control the family-wise error rate due multiple comparisons, a Bonferroni correction was applied.ResultsOn unit B, outdoor space inaccessibility was significantly associated with increased IM PRN use (mean difference = 1.57 orders/day, 95% CI [0.81, 2.33]), increased seclusion and restraint (mean difference = 0.63 orders/day, 95% CI [0.35, 0.91]), and decreased CO (mean difference = 0.40 orders/day, 95% CI [0.17, 0.63]), with no significant change in PO PRN. On unit A, outdoor space inaccessibility was associated with an increase in PO PRN use (mean difference = 0.64 orders/day, 95% CI [0.26, 1.02]), while IM PRN, seclusion and restraint, and CO did not show any statistically significant increase.ConclusionThe loss of accessible outdoor space appears to influence general adult psychiatric patients more broadly, contributing to an increased reliance on restrictive interventions. This is hypothesized to be due to reduced opportunities for self-regulation, personal space, and distancing from stressors. Staff perceptions of limited environmental de-escalation options may also play a role in intervention use. Geriatric patients, due to their inherent lower mobility and activity levels, showed an increase in PO PRN use. These findings underscore the potential role of accessible outdoor spaces in promoting patient well-being and potentially minimizing the need for coercive measures in acute psychiatric settings.